2020
DOI: 10.1029/2020gl087085
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Amplification of Global Warming Strengthened by Sunlight Oxidation of Permafrost Carbon to CO2

Abstract: Once thawed, up to 15% of the ∼1,000Pg of organic carbon (C) in arctic permafrost soils may be oxidized to carbon dioxide (CO 2) by 2,100, amplifying climate change. However, predictions of this amplification strength ignore the oxidation of permafrost C to CO 2 in surface waters (photomineralization). We characterized the wavelength dependence of permafrost dissolved organic carbon (DOC) photomineralization and demonstrate that iron catalyzes photomineralization of old DOC (4,000-6,300 a BP) derived from soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 41 publications
8
67
0
Order By: Relevance
“…Research has continued to quantify the permafrost carbon feedback that involves release of greenhouse gases from thawing permafrost in the Arctic [ 1 ]. Experiments on the wavelength dependence of the photodegradation of dissolved organic carbon (DOC) in permafrost indicated that also UV-A radiation was most efficient [ 314 ]. Laboratory manipulations indicated that variability in the photodegradation may be attributable to iron catalysed photoreactions of old DOC derived from soil lignin and tannin in the melted permafrost.…”
Section: Biogeochemical Cycles In the Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has continued to quantify the permafrost carbon feedback that involves release of greenhouse gases from thawing permafrost in the Arctic [ 1 ]. Experiments on the wavelength dependence of the photodegradation of dissolved organic carbon (DOC) in permafrost indicated that also UV-A radiation was most efficient [ 314 ]. Laboratory manipulations indicated that variability in the photodegradation may be attributable to iron catalysed photoreactions of old DOC derived from soil lignin and tannin in the melted permafrost.…”
Section: Biogeochemical Cycles In the Environmentmentioning
confidence: 99%
“…Laboratory manipulations indicated that variability in the photodegradation may be attributable to iron catalysed photoreactions of old DOC derived from soil lignin and tannin in the melted permafrost. Rates of CO 2 photoproduction from permafrost DOC were twofold higher than for modern DOC [ 314 ]. Model predictions of future net loss of ecosystem carbon from thawing permafrost do not include the loss of CO 2 to the atmosphere from DOC photodegradation.…”
Section: Biogeochemical Cycles In the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNR of 880 was determined based on the ratio of the maximal amplitude of measured CO 2 absorbance to the 1-σ background noise. In addition, the integral absorbance (τ) was obtained to be 2.5 × 10 −2 , and CO 2 concentration was calculated to be 458.89 ppm, according to Equation (5). Therefore, the minimum detection limit was 0.52 ppm, which confirms that the system can be used to measure the atmospheric CO 2 concentration.…”
Section: Measurements and Resultsmentioning
confidence: 74%
“…Anthropogenic emissions of greenhouse gases (GHGs) have a significant impact on global warming, and carbon dioxide (CO 2 ) and methane (CH 4 ) account for 66% and 16% of radiative forcing, respectively [ 1 , 2 , 3 ]. During the last decade (2009–2019), CO 2 concentrations increased at the fastest observed decadal rate of change (2.4 ppm/year), which is higher than that during of any previous decade since direct atmospheric concentration measurements began in 1958 [ 4 , 5 ]. Measurement of the atmospheric CO 2 column concentrations is valuable for understanding regional carbon emissions, sources, and sinks [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%